2011
DOI: 10.1111/j.1475-4983.2010.01000.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and systematics of anthracomartidae (Arachnida: Trigonotarbida)

Abstract: X-ray microtomography (XMT) was applied to three species of the extinct arachnid order Trigonotarbida, hosted in siderite nodules from the late Carboniferous Brit-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 27 publications
(109 reference statements)
3
31
0
Order By: Relevance
“…Other Palaeozoic records, including a long-legged fossil from the Early Carboniferous (~340 Myr) of Scotland 6 , appear superficially modern, but remain too poorly preserved to allow an unequivocal resolution of their affinities. Recent studies have demonstrated the efficacy of applying µCT to three-dimensionally preserved, siderite (FeCO 3 ) hosted Carboniferous arthropod fossils [7][8][9] . Thus such concretions, common in the Euamerican Coal Measures, are among the most promising taphonomic windows for the high-fidelity preservation of Opiliones.…”
mentioning
confidence: 99%
“…Other Palaeozoic records, including a long-legged fossil from the Early Carboniferous (~340 Myr) of Scotland 6 , appear superficially modern, but remain too poorly preserved to allow an unequivocal resolution of their affinities. Recent studies have demonstrated the efficacy of applying µCT to three-dimensionally preserved, siderite (FeCO 3 ) hosted Carboniferous arthropod fossils [7][8][9] . Thus such concretions, common in the Euamerican Coal Measures, are among the most promising taphonomic windows for the high-fidelity preservation of Opiliones.…”
mentioning
confidence: 99%
“…Note that recent work has recognised numerous generic synonyms among the Anthracomartidae (Garwood & Dunlop 2011) and future revisions are likely to reduce the total number of genera still further. For completeness, Eurymartus Matthew, 1895 andElaverimartus Petrunkevitch, 1953 are now regarded as nomina dubia -see Dunlop & Miller (2007), and Raeßler (1998) and Dunlop et al (in press) for respective explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Hirst 1923;Shear et al 1987;Fayers et al 2005;Dunlop et al 2009;Garwood and Dunlop 2010) and from early diagenetic siderite concretions, e.g. from the Upper Carboniferous Coseley Lagerstätte, UK (Garwood et al 2009;Garwood and Dunlop 2011). Trigonotarbids are superficially spider-like arachnids with a body divided into a prosoma, which is covered by the carapace (or prosomal dorsal shield), and an opisthosoma composed of 12 segments (e.g.…”
Section: Introductionmentioning
confidence: 98%